Longitudinal associations of long-term exposure to ultrafine particles with blood pressure and systemic inflammation in Puerto Rican adults. - Corlin, Laura.; Woodin, Mark.; Hart, Jaime E.; Simon, Matthew C.; Gute, David M.; Stowell, Joanna.; Tucker, Katherine L.; Durant, John L.; Brugge, Doug. (2018)
Background: Few longitudinal studies have examined the association between ultrafine particulate matter (UFP, particles ; Keywords: Ultrafine particulate matter, Blood pressure, C-reactive protein, Susceptible populations, Exposure assessment, Hispanic.; Springer Open.